Rapid Combination Therapy for Major Depression SNT with Stellate Ganglion Block in a Multicenter RCT - Wu, Peng (Pacific International Journal, 2025)
This randomized controlled trial of 90 adults with Major Depressive Disorder (MDD) found that combining Stanford Neuromodulation Therapy (SNT) with Stellate Ganglion Block (SGB) yielded significantly superior antidepressant effects compared to either treatment alone. At the primary endpoint of Week 4, the SNT+SGB combination produced a significantly greater reduction in depressive severity on the HAMD-17 than both SGB monotherapy and SNT monotherapy, with a more rapid onset of action and higher response rates, all while maintaining a favorable safety profile. These results demonstrate the clinical potential of a combined mechanism approach that engages both neural circuit and autonomic targets for a more effective treatment of MDD.